-x+3y=-6

Add x to both sides of the equation.

3y=-6+x

Divide each term by 3 and simplify.

Divide each term in 3y=-6+x by 3.

3y3=-63+x3

Cancel the common factor of 3.

Cancel the common factor.

3y3=-63+x3

Divide y by 1.

y=-63+x3

y=-63+x3

Divide -6 by 3.

y=-2+x3

y=-2+x3

y=-2+x3

The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.

y=mx+b

Reorder -2 and x3.

y=x3-2

Rewrite in slope-intercept form.

y=13x-2

y=13x-2

Find the values of m and b using the form y=mx+b.

m=13

b=-2

The slope of the line is the value of m, and the y-intercept is the value of b.

Slope: 13

y-intercept: -2

Slope: 13

y-intercept: -2

Choose 0 to substitute in for x to find the ordered pair.

Replace the variable x with 0 in the expression.

f(0)=03-2

Simplify the result.

Divide 0 by 3.

f(0)=0-2

Subtract 2 from 0.

f(0)=-2

The final answer is -2.

-2

-2

The y value at x=0 is -2.

y=-2

y=-2

Choose 3 to substitute in for x to find the ordered pair.

Replace the variable x with 3 in the expression.

f(3)=33-2

Simplify the result.

Divide 3 by 3.

f(3)=1-2

Subtract 2 from 1.

f(3)=-1

The final answer is -1.

-1

-1

The y value at x=3 is -1.

y=-1

y=-1

Create a table of the x and y values.

xy0-23-1

xy0-23-1

Graph the line using the slope and the y-intercept, or the points.

Slope: 13

y-intercept: -2

xy0-23-1

Graph -x+3y=-6